A propeller-shaped perylene diimide hexamer as a nonfullerene acceptor for organic solar cells. Issue 35 (24th August 2018) - Liu, Juncheng; Xie, Sufei; Feng, Shiyu; Li, Miao; Wu, Liangliang; Xu, Xinjun; Chen, Xuebo; Li, Cuihong; Bo, Zhishan
Abstract : A novel propeller-shaped molecule (HPB-PDI6 ) was synthesized via Co2 (CO)8 -catalyzed cyclotrimerization and used as an acceptor for organic solar cells (OSCs). Devices based onPTB7-Th :HPB-PDI6 achieved a PCE of 6.63% with a V oc of 0.92 V, a J sc of 15.11 mA cm −2, and an FF of 48.0%. Abstract : A novel propeller-shaped molecule (HPB-PDI6 ) with a hexaphenylbenzene (HPB) core and six peripheral PDI units was synthesized via Co2 (CO)8 -catalyzed cyclotrimerization and used as an acceptor for organic solar cells (OSCs). The intriguing geometry of the HPB core and the spatial repulsion of the PDI rings created a twisted three-dimensional propeller-shaped conformation forHPB-PDI6 . The propeller-shaped conformation could prevent the acceptor molecules from forming large aggregates in the active layer. As expected, thePTB7-Th :HPB-PDI6 blend films show a favorable morphology as well as high and balanced charge carrier mobility. Devices based onPTB7-Th :HPB-PDI6 achieved a PCE of 6.63% with a V oc of 0.92 V, a J sc of 15.11 mA cm −2, and an FF of 48.0%. Our results have demonstrated that the easily prepared propeller-shapedHPB-PDI6 could be a promising acceptor for high efficiency organic solar cells.